Nitrogen addition strengthens the stabilizing effect of biodiversity on productivity by increasing plant trait diversity and species asynchrony in the artificial grassland communities - Suonan, Ji; Lu, Xuwei; Li, Xiaona; Hautier, Yann; Wang, Chao (Frontiers in Plant Science, 2023)
Nitrogen (N) enrichment usually weakens the stabilizing effect of biodiversity on productivity. However, previous studies focused on plant species richness and thus largely ignored the potential contributions of plant functional traits to stability, even though evidence is increasing that functional traits are stronger predictors than species richness of ecosystem functions.We conducted a common garden experiment manipulating plant species richness and N addition levels to quantify effects of N addition on relations between species richness and functional trait identity and diversity underpinning the 'fast-slow' economics spectrum and community stability.Nitrogen addition had a minor effect on community stability but increased the positive effects of species richness on community stability. Higher Increasing community stability was found in the species-rich communities dominated by fast species due to substantially increasing temporal mean productivity relative to its standard deviation. Furthermore, enhancement in 'fast-slow' functional diversity in species-rich communities dominated by fast species under N addition increased species asynchrony, resulting in a robust biodiversity-stability relationship under N addition the artificial grassland communities.The findings demonstrate mechanistic links between plant species richness, 'fastslow' functional traits, and community stability under N addition, suggesting that dynamics of biodiversity-stability relations under global changes are the results of species-specific responses of 'fast-slow' traits on the plant economics spectrum.